The Effect Of High-Intensity Interval Training And Fartlek On Vo2max Players U15 And U23 Pamoso Football School - Muhammad Sopyan; Bambang Budi Raharjo; Donny Wira Yudha Kusuma (JUARA : Jurnal Olahraga, 2023)
The purpose of this study was to analyze the differences in the effect of high-intensity interval training and fartlek on the VO2max of players u15 and u23 at the Pamoso football school in Majene Regency, to analyze the differences in VO2max of players U15 and U23 in high-intensity interval training and fartlek, to analyze the interaction between high-intensity interval training exercises and fartlek with age against the vo2max football player Pamoso Majene District football school. This study used an experimental method with a factorial experimental design research design. This study totaled 38 people, 18 players U15 and 20 players U23 and formed into four groups: high-intensity interval training U15 and U23 with fartlek U15 and U23. The results showed an increase in VO2Max in high-intensity interval training for U15 players with an average of 12.167. At the same time, U23 obtained an average pre-test of 36.820 and a post-test of 47.840, with a difference of 11.02. the U15 fartlek group, on the study's results, obtained 37,533 pre-tests and 49,467 post-test with a distinction of 11,943. Fartlek U23 received an average pre-test of 37.140 and post-test of 47.810 with a difference of 10.67, and there was no interaction between training and age on the increase in VO2Max of Pamoso soccer school players. Based on the study's results, there is no difference in growth between training high intensity and fartlek, and both increase the player's VO2 max. There is a difference in the rise in VO2Max for U15 and U23 players; U15 players experienced a 32% higher VO2Max increase than U23 players, who increased 29%. And there was no interaction between high-intensity interval training and fartlek exercises with the age of the players on the increase in vo2max of the Pamoso football school players, Majene Regency.